The Effect of Leadership Education and Training on Structural Promotion: the Mediating Role of Competence Among Civil Servants in the Indonesian National Police - Aries Ferdhita Hariawan; Nanik Kustiningsih; Sundjoto (Jurnal Ragam Pengabdian, 2026)
This study examines the effect of leadership education and training on structural promotion among civil servants in the Indonesian National Police, with competence as a mediating variable. In the context of public sector reform, leadership training programs are expected to support a merit-based promotion system by enhancing individual competence. However, empirical evidence indicates that leadership training does not always lead directly to career advancement. This study aims to provide empirical clarification by analyzing both direct and indirect relationships among leadership training, competence, and structural promotion. A quantitative approach was employed using survey data collected from 121 civil servants working across 29 units of the East Java Regional Police Headquarters. The data were analyzed using Partial Least Squares– Structural Equation Modeling (PLS-SEM) with WarpPLS 7.0. Leadership education and training were measured through curriculum relevance, learning methods, evaluation systems, instructor quality, and program management. Competence was assessed based on managerial, leadership, and technical dimensions, while structural promotion was measured using both perceptual indicators and objective career data. The results show that leadership education and training do not have a significant direct effect on structural promotion. However, leadership training has a significant positive effect on competence, and competence has a strong positive effect on structural promotion. Furthermore, competence fully mediates the relationship between leadership education and training and structural promotion. These findings indicate that leadership training contributes to career advancement only when it effectively enhances measurable competence. This study contributes to the literature on human capital and public sector human resource management by emphasizing the central role of competence in translating training investments into career outcomes. Practically, the findings suggest that promotion systems within the Indonesian National Police should strengthen the integration between leadership training outcomes, competency assessment, and merit-based promotion mechanisms.